Peran Kulit Nanas Sebagai Bioaktivator Dan Penambahan Biochar Tempurung Kelapa Dalam Meningkatkan Hasil Produksi Tanaman Kedelai (Glycine max (L) Merrill) - Andini Lutfiah; Purity Sabila Ajiningrum (Universitas PGRI Adi Buana Surabaya, 2020)
The low soybean production is caused by many limiting factors, including low soil fertility. This is influenced by the use of chemical fertilizers which is a trend among farmers. Therefore, to overcome the above problems is to utilize pineapple peel waste as a bio-activator and the addition of coconut shell biochar as a medium. This study aims to determine the effect of various concentrations of bioactivator waste from pineapple peels on growth, total chlorophyll content and soybean production. The method used is an experimental method carried out at the Green House of the Faculty of Science and Technology, Universitas PGRI Adi Buana Surabaya. The design used was a factorial design (6x5) arranged in a completely randomized design (CRD) consisting of 6 treatments. Treatment 1 was negative control (0%), treatment 2 positive control (EM4), treatment 3 bioactivators 10%, treatment 4 bioactivators 20%, treatment 5 bioactivators 30%, treatment 6 bioactivators 40%. Each treatment was repeated 5 times so that 30 experimental pots were needed. The results showed a significant effect on production at a concentration of 30%. Keywords : Soybean (Gycine max (L.) Merrill), Pineapple Skin Bioactivator, Coconut Shell Biochar